2018
DOI: 10.1126/science.aat6576
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide de novo risk score implicates promoter variation in autism spectrum disorder

Abstract: Whole-genome sequencing (WGS) has facilitated the first genome-wide evaluations of the contribution of de novo noncoding mutations to complex disorders. Using WGS, we assess genetic variation from 7,608 samples in 1,902 autism spectrum disorder (ASD) families, identifying 255,106 de novo mutations. In contrast to coding mutations, no noncoding functional annotation category, analyzed in isolation, is significantly associated with ASD. Casting noncoding variation in the context of a de novo risk score across mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
301
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(322 citation statements)
references
References 52 publications
20
301
1
Order By: Relevance
“…An average of 60 high quality DNVs per proband were identified, which includes 55.2 SNVs and 4.8 indels per proband (Table S2). The number of DNVs identified in this study is similar to the number of DNVs identified per proband in previous GS studies on neurodevelopmental disorders 4,11,37 . It has been shown that de novo copy number variants (CNVs) play a significant role in severe ID 4 .…”
Section: Genome Sequencing and Identification Of De Novo Variantssupporting
confidence: 86%
See 3 more Smart Citations
“…An average of 60 high quality DNVs per proband were identified, which includes 55.2 SNVs and 4.8 indels per proband (Table S2). The number of DNVs identified in this study is similar to the number of DNVs identified per proband in previous GS studies on neurodevelopmental disorders 4,11,37 . It has been shown that de novo copy number variants (CNVs) play a significant role in severe ID 4 .…”
Section: Genome Sequencing and Identification Of De Novo Variantssupporting
confidence: 86%
“…Aggregation of a minority of disease-causing variants with the majority of benign regulatory variants nullifies any signal from disease-causing variants in non proteincoding genomic regions in disease cohorts. It is noteworthy that in protein coding regions of the genome only protein-truncating variants, but not other protein-coding variants, show significant enrichment in neurodevelopmental disorders 11,67 . The analysis of DNVs in selected monogenic phenotypes provides a powerful analysis instrument, because it can focus on a relatively small number of variants that have increased likelihood of being disease-causing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the utility of this procedure for studying human disease, we retrieved a recent dataset of 1902 quartet families from the Simons Simplex Collection (28) with whole genome sequencing of a mother, father, child affected by autism, and unaffected sibling. In these data, the offspring have an average of 67 de novo mutations, which have a slight enrichment in promoters (29). Recent work demonstrated that variant effect predictions further differentiate autism cases from their unaffected sibling controls (30).…”
Section: Mouse-trained Models Highlight Mutations Relevant To Human Nmentioning
confidence: 99%